Creative Problem Solving: Bagaimana Pengaruhnya terhadap Kreativitas Siswa? - Indah Purnama Sari; Adri Nofrianto; Mira Amelia Amri (Jurnal Elemen, 2017)
This study aims to determine how the students' creativity in solving math problems in class X if given the problems that are non-routine. This type of research is using qualitative approach. Subjects in this study were selected three students of 22 male students of class X is based on tests of mathematical ability. Data is collected in the form of two different time solving tests and interviews. Data were analyzed using three steps, namely data reduction, the data display and conclusion drawing. Based on data analysis, found that the learning model creative problem solving can improve students' creativity in the form of an increase in problem-solving ideas are included in the components of fluency. In addition, given the increased student solutions differ from other research subjects are included in the components of originality. However, for component flexibility, only able to provide a variety of different ways to solve the problem, although it has not achieved until the end of the settlement proper.